The aid-nutrition link – Does targeted development assistance related to food systems matter?. (February 2023) - Kornher, Lukas; Kubik, Zaneta; Chichaibelu, Bezawit Beyene; Torero Cullen, Maximo
Highlights: We examine the relevance of targeted ODA related to food systems for improving food and nutrition security and achieving SDG 2. We find a significant contribution of food system related ODA to the reduction in the PoU and child nutrition since 2000. Food and nutrition security indicators are stronger and more immediate associated with food system related ODA than with overall ODA. Food system related ODA is mainly associated with improvements in caloric supply and lower food price inflation but not with food production. Abstract: In this study, we discuss and examine the relevance of food system related official development assistance (ODA) for improving food and nutrition security. We hypothesize that given the relationship between agricultural growth and poverty reduction as well as food and nutrition security, aid attributed to food systems could have a stronger and more immediate impact on food and nutrition security than overall aid. We look at the long-run effects and we apply an instrumental variable approach to address reverse causality. Our instrumentation strategy follows the related literature in estimating the supply of aid from the donors' point of view but also uses a dummy variable for the common continental origin of donor and recipient country and the level of diplomatic representation of the donor country as novel zero-stage instruments. We find a statistically significant and economically meaningful contribution of food system related ODA to hunger and malnutrition reduction since 2000. This has important implications for donor countries, particularly those that focus on the fight against hunger in their development cooperation strategies.